A COMPARATIVE STUDY OF OPAQUE PHASES IN QUINGZHEN (EH3) AND MACALPINE HILLS 88136 (EL3): REPRESENTATIVES OF EH AND EL PARENT BODIES - Lin Y.; El Goresy A. (My University, 2002)
Opaque minerals in the Qingzhen (EH3) and MacAlpine Hills (MAC) 88136 (EL3) enstatite chondrites were studied and compared with other EH and EL chondrites. All opaque minerals usually occur in multi-sulfide-metal clasts and nodules in the matrix between chondrules (El Goresy et al., 1988). The higher abundance of opaque minerals, the occurrence of niningerite and various alkali-sulfides (e.g., caswellsilverite, phases A and B, djerfisherite) are diagnostic criteria for EH chondrites, while alabandite is characteristic for EL chondrites. In addition, EH chondrites are characterized by enrichments of Si in both kamacite and perryite, and alkali elements in sphalerite and chalcopyrite. The Mn contents of daubreelite and sphalerite are lower in EH than in EL chondrites. These are consistent with lower oxygen fugacity and higher H2S fugacity of EH than EL chondrites. In contrast, the discovery of sphalerite and Zn-rich daubreelite in MAC 88136 indicates that their absence in EL6 chondrites is probably related to thermal metamorphism in the parent body. Schreibersite microspherules are commonly enclosed in most sulfides in Qingzhen, but are absent in MAC 88136. They were once molten, and probably predated all sulfide host phases. The petrographic setting and chemical compositions of the sulfide hosts of the schreibersite microspherules in EH3 chondrites are consistent with formation by condensation. The earliest sulfide condensates oldhamite and niningerite occupy the interiors of the clasts and nodules, whereas the rims consist of troilite and djerfisherite. In addition, in Qingzhen, some other troilite, djerfisherite and sphalerite assemblages coexist with perryite. They were produced by sulfurization of metallic Fe-Ni in the nebula. In MAC 88136, sulfurization of Si-bearing Fe-Ni metal is less pronounced, and it produced troilite, schreibersite and less abundant perryite. Two kinds of normal zoning and a reverse zoning trends of niningerite, and both normal and reverse zoning of sphalerite were found in clasts and nodules in Qingzhen. The coexistence of normal and reverse zoning profiles in niningerite grains in the same meteorite strongly suggests that they formed before accretion in the parent body, because an asteroidal metamorphic or an impact event in the parent body would have erased these contrasting profiles and destroyed the textural settings. In contrast, alabandite in MAC 88136 shows only normal zoning, with the FeS content decreasing to 9.3 mol% toward troilite, indicating very slow cooling at low temperature.